Firework Algorithm For Multi-Objective Optimization Of A Multimodal Transportation Network Problem - Mnif, Mouna; Bouamama, Sadok (Procedia computer science, 2017)
This study suggests a multi-objective firework algorithm based on the Pareto-dominance method in order to select the optimistic solution from the multimodal transportation problem. The aim is to determine a shortest and efficient itinerary of satisfying a certain set of demands and operational constraints. Several publications have appeared in recent years documenting the transportation network analysis. This fact reflects the importance and complexity of this problem. In order to reach a sustainable planning in a rather complicated transport system, it is of high interest to use an approach that belongs to the field of artificial intelligence method. This paper introduces a new multi-objective approach based on firework algorithm that generates n solutions which are then selected according to the Pareto-dominance which is the best compromise between goals. Finally, we present our obtained experimental results, then we compare them with the obtained results by Cplex in order to prove the efficiency of this algorithm.